Effectiveness of Allowance of Auditor Travel Cost - mahfudin, mahfudin; Febrianto, Andrie Mulya (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2020)
This study is lifted from the specific characteristics of official travel for the auditor compared to other official travel, so there is a need to determine the specificity of input cost standards. The purpose of this study is to look at the effectiveness of the policy of official travel costs especially allowance for auditors on the quality of performance and finance. The study was conducted with a qualitative approach. Respondents in this study were auditors from 4 inspectorate general units and 10 work units which were audited by the auditors (auditees). The results of this study indicate that the policy of official travel costs is still quite effective in supporting the implementation of supervision/ inspection. Supervision/inspection of auditors is also recognized to improve the quality of performance and financial auditees. It should be noted that the provision of an examination allowance in the same office location contrasts with the provision of performance allowances for auditors, although the allowance is one of the motivations for auditors to conduct audits at the head office.